DIFFICULTIES IN THE APPLICATION OF INTERACTIVE TEACHING METHODS - Olga V. Lomakina (Moscow Polytechnic University, 2016)
The article is an attempt to analyze the difficulties in the use of interactive methods in the educational process from the positions of teachers and students.